P80 Bilateral superior caval vein associated with unroofed coronary sinus. (6th June 2017) - Cinteza, Eliza; Balgradean, Mihaela; Giugno, Luca; Giamberti, Alessandro; Filip, Cristina; Duica, Gabriela; Nicolae, Georgiana; Nicolescu, Alin
Abstract : Unroofed coronary sinus (UCS) is an extremely rare malformation. Bilateral superior vena cava is much more rare than the isolated form of UCS (only eight cases reported in literature). We present the case of a teenager, aged 12 years, overweight, who presented with exertional dyspnea. Clinical and echocardiographic evaluation highlights systemic saturation decreased to 93%, and dilated right cardiac chambers. It raises the suspicion of a complex systemic venous malformation back into the left atrium and left-to-right shunt. After complex investigation, by transesophageal echocardiography with contrast administration, angio CT multi-slice, cardiac catheterization, the diagnosis was made and the patient underwent surgical correction: attaching left superior vena cava to the right atrial appendage, anterior wall septation of the coronary sinus with patch of bovine pericardium on the absent entire length. Conclusion: This is an example of an extremely rare case in which the clinical signs are mild or even absent that after complete diagnosis underwent directly into the operating room due to the risk of cianosis, systemic embolization, cerebral abscess, pulmonary hypertension, Eisenmenger syndrom.